Upaya Kepala Sekolah Mengintegrasikan Kurikulum Pendidikan Agama Islam Berbasis Pesantren Kedalam Kurikulum Sekolah - Ahmad Budiyono (Lembaga Penelitian, Penerbitan dan Pengabdian (LP3M) IAI Al-Urwatul Wutsqo Jombang, 2018)
Schools with pesantren basis now is for integrating public education with pesantren. This study examines the pesantren-based PAI curriculum model integrates the curriculum into a national standard PAI curriculum. This is a head master effort as a leader who conducts two curriculums that is national and pesantren curriculum. The aim is in order to create a strong and superior generation in the fields of IMTAQ, science and technology development, and morality. PAI collaborated with pesantren subjects, is in accordance with national and pesantren curriculum. Pesantren curriculum is including Nahwu Shorof, Arabic, SKI and Kedaruluman, Aqidah-Akhlak, Fiqh, Qur'an Hadith, Tajwid. All of these are combined with descriptions of the books in the pesantren. Besides religious application programs including Reading Al-qu'an, such practices activites as tahlil, istighosah and dhuha. From the research results, the researcher recommends the Religion and national education ministry to provide training for teachers about the model integrated learning, especially for the institutions under the pesantren, then the school principals have to strive to integrate the pesantren curriculum into formal schools.